Distributed control system for a parallel‐connected AC/DC converters. Issue 3 (1st March 2013) - Chunkag, Viboon; Kanthaphayao, Yutthana; Kamnarn, Uthen
Abstract : This study presents a distributed control system for parallel‐connected AC/DC converters. The proposed system composed of isolated CUK AC/DC converters which each converter has its own controller and a simple current‐sharing circuit. The purposes are modular system and distributed control. The control system consists of an analogue circuit and a microcontroller. The analogue circuit is used for a current sharing and control the input current to be in‐phase with the input voltage. The microcontroller is used for generating the control signals to adjust gain of the current sharing and to control the output voltage. The performance evaluation was conducted through the simulation and experimental results, on a three‐module parallel‐connected, with a 540 W load, a − 48 V of DC bus output voltage. The performance of the proposed system has been achieved as follows: the current sharing is quite well; the redundant operation can be implemented in this system, the fast transient response and a high‐power factor.